Olhos d'água de conceição evaristo: a voz da mulher negra na corda bamba da tradução - Saramin, Alessandra (2019)
The aim of this work is to translate and analyze the book of the afro-brazilian author Conceição Evaristo: Olhos d’Agua. This book is a collection of short novels that gives a clear picture of marginalized people in the modern Brazilian society. The analysis of this work started considering the themes of the works of Conceição Evaristo. She uses the term “escrevivência” (writing the life) to combine in one word all the themes that are recurring in her works. Starting from the other novels and poems written by Conceição Evaristo, in the second chapter of this work, the most frequent topics are discussed: the comparison between life and death, the condition of life of marginalized people, the life of afro-brazilian women trying to survive in a racist society, the importance and representation of their bodies and their effort to speak up to find an identity. All these elements are important themes in her works. In Olhos d’água most of the main characters are women that, together with the male protagonists and the other characters, live in favelas, as marginalized people of the Brazilian society.